Randomized comparison of quinine-clindamycin versus artesunate in the treatment of falciparum malaria in pregnancy. - Mcgready, R; Cho, T; Samuel; Villegas, L; Brockman, A; van Vugt, M; Looareesuwan, S; White, N; Nosten, F (2001)
In areas where multidrug-resistant Plasmodium falciparum (MDR-Pf) is prevalent, only quinine is known to be safe and effective in pregnant women. On the western border of Thailand, 7 days of supervised quinine (30 mg/kg daily) cures two-thirds of P. falciparum-infected women in the 2nd and 3rd trimesters of pregnancy. Artesunate is effective against MDR-Pf and the limited data on its use in pregnancy suggest it is safe. An open randomized comparison of supervised quinine (10 mg salt/kg every 8 h) in combination with clindamycin (5 mg/kg every 8 h) for 7 days (QC7) versus artesunate 2 mg/kg per day for 7 days (A7) was conducted in 1997-2000 in 129 Karen women with acute uncomplicated falciparum malaria in the 2nd or 3rd trimesters of pregnancy. There was no difference in the day-42 cure rates between the QC7 (n = 65) and A7 (n = 64) regimens with an efficacy of 100% in both, confirmed by parasite genotyping. The A7 regimen was also associated with less gametocyte carriage; the average person-gametocyte-weeks for A7 was 3 (95% CI 0-19) and for QC7 was 39 (95% CI 21-66) per 1000 person-weeks, respectively (P < 0.01). There was no difference in gastrointestinal symptoms between the groups but there was significantly more tinnitus in the QC7 group compared to the A7 group (44.9% vs 8.9%; RR 5.1; 95% CI 1.9-13.5; P < 0.001). The favourable results with quinine-clindamycin mean that there is a useful back-up treatment for women with falciparum malaria who experience quinine and artesunate failures in pregnancy. Adherence to the 7-day regimen and cost (US$18.50 per treatment) are likely to be the main obstacles to this regimen.